SURVIVING SOLITUDE: THE TREACHEROUS EXPEDITION OF A CHILD FOLLOWING A MATERNAL CATASTROPHE IN THE FILM 'PIHU' - Ann Jacob1 , Dr. S Dinesh Babu2, (Chelonian Research Foundation, 2023)
The theatrical work titled "Pihu," directed by Vinod Kapi, portrays an emotional storyline that revolves around a toddler who experiences a day of solitude, unaware of the untimely demise of her mother due to an overdose of sleeping medication. The film emphasizes the profound consequences of Maternal conflict and mental health challenges on the developmental trajectory of a young child. This analysis aims to examine the various dangerous circumstances that the child experiences and highlight the film's importance as a medium for drawing attention to the significant consequences of suicide, domestic violence, and despair. This study is to provide a comprehensive analysis of the film's narrative, to shed light on the difficulties and obstacles encountered by a child. The goal is to serve as an educational resource, aimed at increasing awareness regarding the significant psychological effects that arise from parental conflicts on a child's mental well-being. The significance of this research on 'Pihu' lies in its examination of the difficulties encountered by a child following the suicide of their mother. Moreover, it acts as a catalyst for deeper discussions concerning mental health, familial interactions, and the welfare of children in the aftermath of distressing occurrences. The primary objective of this study is to provide significant contributions to professionals, policymakers, and caregivers who are actively engaged in assisting children impacted by comparable situations. Ultimately, the study seeks to promote a more compassionate and knowledgeable approach to addressing the needs of these children and the importance of mental health. Keywords: child well-being, domestic violence, suicide, cinema a platform for awareness, cinema for education, Mental health.